Business Model Canvas Analysis At Tiga Putra Digital Copier - Hidayat, Gustina; Rohimah, Ai; Nurfalah, Muhamad Azriel; Putra, Rizky Adi (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2026)
This study aims to analyze the business development strategy of the Fotokopi Tiga Putra MSME in Sumedang using the Business Model Canvas (BMC) approach. Amidst business competition and the digital era, photocopying businesses face challenges such as changing paperless trends and price competition. The research method used was descriptive qualitative, with data collected through observation and in-depth interviews with the business owner. The analysis shows that Fotokopi Tiga Putra has the advantages of a strategic location and 24-hour service, but weaknesses include limited human resources and conventional marketing. By mapping the nine BMC elements, a development strategy was formulated, including creating a Google Business profile, optimizing social media for promotion, adding digital services, and implementing a competitive pricing strategy to maintain and expand market share among students and the general public